2015
DOI: 10.1186/s12917-015-0511-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterisation of bovine corona and toroviruses from Croatian cattle

Abstract: BackgroundBovine coronavirus (BCoV) together with bovine torovirus (BToV), both members of the Coronaviridae family, order Nidovirales are the most common viral enteric pathogens. Although studied separately, their joint occurrence and the molecular diversity in cattle in Croatia have not been investigated.MethodsA survey is carried out on 101 fecal samples from diarrheic young and adult cattle during the 3-year period from i) one large dairy herd, ii) four small herds and iii) three nasal and paired fecal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
(44 reference statements)
2
18
3
Order By: Relevance
“…BToV was originally isolated from diarrheic calves (Lojkic et al 2015) and is now distributed worldwide (Gulacti et al 2014;Hoet et al 2002;Koopmans et al 1991;Park et al 2008). Our results revealed that the prevalence of BToV was 2.2%, which was slightly lower than that previously reported in the ROK (Park et al 2008).…”
Section: Discussioncontrasting
confidence: 47%
“…BToV was originally isolated from diarrheic calves (Lojkic et al 2015) and is now distributed worldwide (Gulacti et al 2014;Hoet et al 2002;Koopmans et al 1991;Park et al 2008). Our results revealed that the prevalence of BToV was 2.2%, which was slightly lower than that previously reported in the ROK (Park et al 2008).…”
Section: Discussioncontrasting
confidence: 47%
“…The results of these studies suggest that current BCoV strains circulating in worldwide are diverging from the prototype BCoV isolated in earlier studies and used in vaccines . This can result in the emergency of new clinical syndromes, outbreaks of enteric diseases with higher morbidity and case fatality (similar to the one described in this study), increased detection rates of BCoV in nasal and fecal samples of healthy and ill calves, and the lack of efficacy vaccination protocols . Future studies should focus on investigating the biological, antigenical, and genomical characteristic of BCoV circulating in Canada.…”
Section: Discussionmentioning
confidence: 54%
“…This new field isolate was antigenically and genetically different to previously isolated BCoV strains including those from neonatal diarrhea, reference strains, and the strain in the current modified live vaccine BCoV licence in United States that belong to CoV clade 1. 38 Similar results have been reported in Europe and Asia . In 2012, the BCoV clade 2 strain was recovered from postweaned calves (6–7 months) suffering of severe enteritis with bloody diarrhea; the authors of that study suggested that this clinical syndrome caused by BCoV clade 2 should be added to the already known syndromes caused by BCoV .…”
Section: Discussionmentioning
confidence: 58%
“…Comparably high genetic similarity was also observed between BCoV isolates analyzed in other laboratories. For example, the amino acid identity in the S1 region was over 96 % between Scandinavian isolates (Liu et al, 2006), over 97.5 % between Croatian isolates (Lojkic et al, 2015), simi-lar as between isolates from Korea (Park et al, 2006). Th e amino acid substitutions in isolates analyzed in our work were concentrated in three regions at positions 10-118, 146-179 and the hypervariable region (pos.…”
Section: Figmentioning
confidence: 58%